The Implementation of The Dialogue Method At The Primary School Level From The Perspective Of Socrates' Analysis - Dian, Dian; Daryani, Ari; Supriyanto, Dadang; Safitri, DesiÂ ; Sahal, Eska Hifdiyah (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to analyze the relevance of Socratic analysis in the application of the dialogue method in elementary schools. The research approach uses descriptive qualitative data collection techniques using documentation studies and literature studies related to this research topic. The data analysis technique uses the Miles and Hubmer analysis model, through the stages of data collection, data reduction, data presentation, and drawing conclusions or data validation. The findings in this research are that the application of the dialogue method with Socratic analysis to elementary school students needs to pay attention to the stage of students' cognitive development, where there are two stages of cognitive development for elementary school students, students aged 7-11 years who are generally in grades 1- 5 are at the concrete operational stage of cognitive development. Meanwhile, students aged 11-13 years who are generally in grades 5-6 are at the formal operational cognitive development stage. In applying the dialogue method with Socratic analysis, paying attention to students' cognitive development stages is a necessity because this can influence the level of understanding of students' reasoning and the effectiveness of the dialogue process. Obstacles encountered in the dialogue process with Socratic analysis in elementary schools, the language used needs to be adjusted to students' understanding, and external conditions, namely the environment which is often less supportive.